Computer and library services - Madan, Som Nath. (Delhi, India : Commonwealth, 1987)
With special reference to India; includes directory of computer dealers and computer training centers in India.
Includes index.
Bibliography: p. 122-126.
Keywords: Libraries -- India -- Automation; Computers -- India; Computer industry -- India -- Directories